Graph Theoretic Approaches to Foreign Exchange Operations - Christofides, N.; Hewins, R. D.; Salkin, G. R. (Journal of Financial and Quantitative Analysis, 1979)
Trading in currencies in order to obtain the best possible exchange rate is known as arbitrage and can broadly be divided into three categories:1) Space Arbitrage––transactions to take advantage of discrepancies between rates quoted at the same time in different markets.2) Time Arbitrage––transactions to take advantage of discrepancies between forward margins for different maturities.3) Interest Arbitrage––transactions to take advantage of discrepancies between yield on short-term investments in different currencies. This form of arbitrage can be split into (a) Covered and (b) Uncovered (speculative) interest arbitrage. The former variety uses today's forward rate for forward conversion back into our holding currency; the latter allows the dealer to use the spot rate existing in the future.